Dandismo, estética queer e consumo: sobre a coleção de Dorian Gray e a performance do eu - Andrio Santos (Revista Odisséia, 2025)
Dandyism and its contradictions have helped to ponder about queer identities since the turn of the nineteenth century. The dandy cultivates an aesthetic of appearances, aestheticizing and stylizing the body, which suggests that identity is performative, and undermines heteronormative conceptions towards body, gender, and sexuality. Understanding dandyism as performance (and as a form of protest against modern industrial capitalism) has become the basis for contemporary models of gay identity archetypes discussed by gay and queer studies, as well as for contemporary discussions of politics of style. In this essay, I discuss Chapter IX of Oscar Wilde’s The Picture of Dorian Gray (1890), the novel’s “aesthetic treatise.” In it, Wilde articulates the figure of the dandy Dorian Gray to a queer aesthetic through the experience of collecting rare, exotic, and manufactured items, upheld by the spiritualizing of the senses.